Northern Balinese Nickname System - I Dewa Putu Wijana (Deskripsi Bahasa, 2019)
This paper is intended to describe the Northern Balinese nickname system with focus of attention on the forms and their relation with the owner’s real names, and various references and their connection with the extralinguistic facts of the person they refer to. By using correlational method between the nicknames and the owner’s real names, and between the references and physical, behavioral, and historical realities of the personthey denote to, It is found that there are at least three relation types that hold between the nicknames and the real names, namely arbitrary, formal, and extralinguistic relation type; The nicknames semantically refer to various entities, such as animal and its excrement, physical and mental characteristics, illness, fruit and food, childhood expressions, personal figures, and important events. All of these referents are essentially reflections of cultural realities of the Nothern Balinese community members’ interaction in their new places.